A common life : the wedding story - Karon, Jan (New York : Viking, 2001)
A retired Episcopal rector accepts an interim post on an island off the coast of North Carolina, where new challenges and adventures await him and his wife.
Keywords: City and town life -- Fiction; Domestic fiction